The chiaroscuro woodcut in Renaissance Italy - Takahatake, Naoko, 1977-; Bober, Jonathan; Gabbarelli, Jamie; Griffiths, Antony; Parshall, Peter; Morenus, Linda Stiber; Los Angeles County Museum of Art; National Gallery of Art (U.S.) (Los Angeles, CA : Los Angeles County Museum of Art ; Munich ; New York, NY : DelMonico Books, an imprint of Prestel, 2018)
"The art of the chiaroscuro woodcut is celebrated in this groundbreaking and generously illustrated book. Chiaroscuro woodcuts are among the most immediately appealing of all historic prints, displaying exquisite invention, refined draftsmanship, technical virtuosity, and sumptuous color. Printing two or more woodblocks inked in different tones to create an image, the chiaroscuro woodcut was the earliest, most successful foray into color printing in Europe. Following its invention in Germany, the technique was first adopted around 1516 in Italy where it flourished through the sixteenth century. This novel art form engaged the interests of the most celebrated artists of the Renaissance, including Titian, Raphael, Parmigianino, and Beccafumi, and underwent sophisticated developments in the hands of such master printmakers as Ugo da Carpi, Antonio da Trento, Niccol Vicentino, and Andrea Andreani. Featuring more than 100 prints and related drawings, this book incorporates pioneering art historical research and scientific analysis to present a comprehensive study of the subject. Essays trace its creative origins and evolution, describing both materials and means of production. Brimming with full-color illustrations of rare and beautiful works, this book offers a fresh interpretation of these remarkable prints, which exemplify the rich imagery of the Italian Renaissance"--
The Italian chiaroscuro woodcut : History and technique / Naoko Takahatake -- The origins of the chiaroscuro woodcut / Peter Parshall -- The chiaroscuro woodcut and drawing in sixteenth-century Italy / Jonathan Bober -- The place of the chiaroscuro woodcut within European printmaking / Antony Griffiths -- Catalogue / Naoko Takahatake, with Jonathan Bober, Jamie Gabbarelli, and Linda Stiber Morenus -- Note to the reader -- Ugo da carpi in Venice and Rome c. 1516-17 -- Parmigianino, ugo da carpi, and Antonio da Trento in Bologna c. 1517-30 -- Niccol{grave}o Vicentino and his workshop c. 1540s -- Domenico Beccafumi c. 1540s -- The dissemination of the technique in Italy c. 1530s-80s -- Andrea Andreani c. 1580-1610 -- Recreating the Italian chiaroscuro woodcut / Linda Stiber Morenus.
"Published in conjunction with the exhibition The Chiaroscuro Woodcut in Renaissance Italy. This exhibition was organized by the Los Angeles County Museum of Art, in association with the National Gallery of Art. Exhibition itinerary: Los Angeles County Museum of Art: June 3-September 16, 2018 National Gallery of Art, Washington: October 14, 2018-January 20, 2019"-- Provided by publisher.
Includes bibliographical references (pages 276-280) and index.
Keywords: Wood-engraving, Italian -- 16th century -- Exhibitions; Wood-engraving, Renaissance -- Italy -- Exhibitions; Chiaroscuro -- Exhibitions